2017
DOI: 10.1007/s10910-017-0809-x
|View full text |Cite
|
Sign up to set email alerts
|

Reactant subspaces and kinetics of chemical reaction networks

Abstract: This paper studies a chemical reaction network's (CRN) reactant subspace, i.e. the linear subspace generated by its reactant complexes, to elucidate its role in the system's kinetic behaviour. We introduce concepts such as reactant rank and reactant deficiency and compare them with their analogues currently used in chemical reaction network theory. We construct a classification of CRNs based on the type of intersection between the reactant subspace R and the stoichiometric subspace S and identify the subnetwor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 12 publications
0
21
0
Order By: Relevance
“…As shown in [1], for a PL-RDK on a cycle-terminal network, the kinetic flux subspace coincides with the kinetic order subspaceS M R introduced by Müller and Regensburger in [15]. Moreover, for a MAK system on an RSS network, it coincides with the stoichiometric subspace.Recall also from [1] that a PL-RDK kinetics is called Y-kernel aligned (YKA) if ker Y res ⊂ ker T .…”
Section: Definition 35mentioning
confidence: 58%
See 4 more Smart Citations
“…As shown in [1], for a PL-RDK on a cycle-terminal network, the kinetic flux subspace coincides with the kinetic order subspaceS M R introduced by Müller and Regensburger in [15]. Moreover, for a MAK system on an RSS network, it coincides with the stoichiometric subspace.Recall also from [1] that a PL-RDK kinetics is called Y-kernel aligned (YKA) if ker Y res ⊂ ker T .…”
Section: Definition 35mentioning
confidence: 58%
“…Arceo et al [1] conducted an initial systematic study of the reactant subspace R's connection to kinetic behavior and identified the set of RSS networks as particularly interesting.…”
Section: Definition 10mentioning
confidence: 99%
See 3 more Smart Citations